Ascaris lumbricoides a rare cause gastric perforation: a case report and brief literature review - Tian-Hao Xie; Tian-Hao Xie; Yan Fu; Xiang-Xiang Ren; Xin-Li Sun; Qiang Wang; Qian Sun (Frontiers in Medicine)
Ascaris lumbricoides (AL), a prevalent nematode causing ascariasis, infects millions worldwide, with a higher risk in preschool and school-aged children. Though infections are usually mild, rare and life-threatening complications like gastrointestinal perforation exist. This article documents a case involving a 61-year-old deaf-mute man who presented with a month-long history of epigastric pain accompanied by nausea, anorexia, and constipation. The pain exacerbated, eventually extended to encompass the entire abdomen 4 h prior to being diagnosed with hollow viscus perforation. During the surgical procedure, three live ascarids were discovered within the abdominal cavity, and the jejunum was found to be filled with a large number of ascarids, accompanied by a perforation in the gastric antrum. Subsequently, the ascarids were extracted, and the perforated area was repaired. Postoperatively, the patient underwent anti-infection therapy, acid suppression, gastric mucosa protection, and nutritional support. On postoperative day (POD) 1, a single dose of 400 mg albendazole was administered. Fecal samples on POD 3, 5, and 6 tested positive for AL eggs. The patient recovered smoothly with no evidence of peptic ulcer disease on one-month follow-up endoscopy. Additionally, fecal tests conducted over three consecutive days did not detect any AL eggs. This case highlights the crucial importance of recognizing ascariasis-associated complications and underscores the paramount role of timely surgical intervention in such cases. Meanwhile, this article combines cases of gastrointestinal perforation caused by AL documented in the literature since 1903, elaborates on the epidemiological characteristics, pathogenesis, diagnosis, treatment, and prevention of ascariasis, and analyzes the reasons for the occurrence of such complications.